Development of Science Literacy Competencies of Science Teachers through Participatory Andragogy Approach - Patonah, Siti; Novita, Mega; Indiati, Intan (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
The science literacy in Indonesia is still far below the OECD average, reflecting the challenges of the national education system. The Independent Curriculum highlights the importance of science literacy but faces limited implementation at the local level, including Purbalingga Regency. The activity method used in this community service is Participatory Action Research (PAR).  This community service activity was conducted between February and May 2024 and aimed at improving the science literacy of junior high school science teachers in Purbalingga Regency. It was carried out offline and online webinars with a participatory andragogy approach. The number of participants in the offline session was 116, while 165 people attended the online session. The activities at the online meeting focused on Science learning and literacy-based assessment for junior high school science teachers in Purbalingga Regency, while the online activity focused on Differentiated and science-based science learning for science teachers. The initial analysis identified problems in science learning that were overcome with intensive training and assistance based on science literacy. This community service can significantly improve participants' understanding, with the post-test score of the seminar on February 17, 2024, reaching an average of 88.46, and the webinar on May 11, 2024, recording 86.54. The evaluation showed effective support for the Independent Curriculum with the integration of science literacy in science learning. This community service not only improves the science literacy of science teachers in Purbalingga but also supports the vision of inclusive education and the development of HOTS. Sustainable implementation is expected to help prepare a competent generation for a better future.